Australian Solidarity Towards Southern Pacific Regional Development - Ruyuan Liu (Journal of Management Practices, Humanities and Social Sciences, 2019)
The aim of this research is to study the Australian position on regional development. This research intends to assess the Australian solidarity towards Southern Pacific development from theoretical, security, economic, and environmental perspectives because of the pertinence of these factors affecting the region and the frequency of terms appeared on Pacific Islands Forum. It argues that Australian regional dedication inclines to rationalist perspectives and not much constructivism. The level of solidarity is relatively low comparing to New Zealand's. This paper conducted a theoretical analysis and specific policy analysis with a comparative study of New Zealand. To illustrate the case, it applies the numeric analysis in aids and qualitative analysis of policy decisions in climate change, regional security, and labor issues. The analysis relies on the rationalistic perspective of Australian economic and security contribution to the region compared with its other overseas activities and with New Zealand's. The indicators are derived from economic and security focus: the total amount of aids, military engagement, and climate improvement. It is concluded that the Australian regional solidarity is not from a constructivist perspective, but a rationalist one. Australian government orientation of cooperation are national-centric, and the current regional integration program is subject to the diminishing power of the United States and the rising power of China in the region.